2022
DOI: 10.1155/2022/7772305
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Beta‐Sitosterol Facilitates GLUT4 Vesicle Fusion on the Plasma Membrane via the Activation of Rab/IRAP/Munc 18 Signaling Pathways in Diabetic Gastrocnemius Muscle of Adult Male Rats

Abstract: Nutritional overload in the form of high-fat and nonglycolysis sugar intake contributes towards the accelerated creation of reactive oxygen species (ROS), hyperglycemia, and dyslipidemia. Glucose absorption and its subsequent oxidation processes in fat and muscle tissues alter as a consequence of these modifications. Insulin resistance (IR) caused glucose transporter 4 (GLUT4) translocation to encounter a challenge that manifested itself as changes in glycolytic pathways and insulin signaling. We previously fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…A decreased level of triglycerides and cholesterol is achieved with LKB1-mediated AMPK activation [ 128 ]. Likewise, β-sitosterol supplementation is proved to facilitate GLUT4 translocation and upregulate insulin sensitivity in HFD-induced diabetic rats, manifested in the increased activity of glycolytic and gluconeogenesis enzymes [ 129 ]. Taken together, these data suggest the promoting effect of β-sitosterol on mitochondrial function and glucose metabolism in the skeletal muscle.…”
Section: Whole Grain Bioactive Compounds In the Regulation Of Skeleta...mentioning
confidence: 99%
“…A decreased level of triglycerides and cholesterol is achieved with LKB1-mediated AMPK activation [ 128 ]. Likewise, β-sitosterol supplementation is proved to facilitate GLUT4 translocation and upregulate insulin sensitivity in HFD-induced diabetic rats, manifested in the increased activity of glycolytic and gluconeogenesis enzymes [ 129 ]. Taken together, these data suggest the promoting effect of β-sitosterol on mitochondrial function and glucose metabolism in the skeletal muscle.…”
Section: Whole Grain Bioactive Compounds In the Regulation Of Skeleta...mentioning
confidence: 99%
“…We obtained the ingredients and target information from database and constructed the ingredient‐ target network, with the major active components being beta‐sitosterol, stigmasterol, kaempferol, luteolin, and formononetin, the former two of which belong to the family of phytosterols, similar to cholesterol in structure and present in plant cell membranes. Many studies have reported that they offer anti‐inflammatory, antidiabetic and antioxidative benefits (Bao et al., 2022; Pei et al., 2022; Qian et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In normal conditions, cellular glucose uptake is facilitated by insulin release with the help of glucose transporter (GLUT4) to the cell’s surface [ 6 ]. We observed significantly elevated activation and phosphorylation of IRS-1, phosphorylation of serine Akt, phosphorylation of threonine Akt, and phosphorylation of threonine AS160 in diet-induced T2DM adipocytes [ 7 ]. Altered GLUT4 translocation results in disrupted uptake of glucose, leading to insulin resistance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%